GAMBARAN PENGETAHUAN IBU NIFAS TENTANG PEMBERIAN VITAMIN A SELAMA MASA NIFAS DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Sellia Juwita (Jurnal Kesehatan Husada Gemilang, 2018)
The cover age of vitamin A delivery on post partumin Indonesia declines from 2006 to 2009 (59 % to 53% of overall postpartum of 30 days post partum). The result sof the survey showed that 10% of postpartumin 2009 experienced night blindness (xeropthalmia) due to vitamin A deficiency. Vitamin A deficiencyin the postpartum is influenced by the lack of knowledge about the needs of vitamin A during the puerperium. This study a imsatrecognizing the description of postpartum knowledge about vitamin A during the puerperium at RSUD Arifin Achmad Riau Province. This research uses a descriptive quantitative research design.The population of this study were all postpartum with a total sample of people.The sample was taken by accidental sampling technique. This research was conducted at RSUD Arifin Achmad Riau Province through question naire instrument.The data analysis is univariate analysis. The results of there search shows that good category of postpartum knowledge is 3 people (4.3%), while suffecient category is 38 people (54.3%), and 29 people(41,4%) for low category. The conclusion of this study is that postpartum knowledge about vitamin A during the puerperium period is in sufficient category.